Characterization of Oral Candida spp. Biofilms in Children and Adults Carriers from Eastern Europe and South America - Anelise Maria Costa Vasconcelos Alves; Beatriz Oliveira Lopes; Ana Caroline Rocha de Melo Leite; Gabriela Silva Cruz; Érika Helena Salles de Brito; Laritza Ferreira de Lima; Lucia Černáková; Nuno Filipe Azevedo; Célia Fortuna Rodrigues (MDPI AG, 2023)
Background: Candida albicans and non-Candida albicans Candida species (NCACs) are known to colonize and invade various tissues, including the oral mucosa. In this work, we aimed to characterize mature biofilms of several Candida spp. clinical isolates (n = 33) obtained from the oral mucosa of children, adults, and elders of Eastern Europe and South America. Methods: Each strain was evaluated for its capacity to form biofilms in terms of total biomass using the crystal violet assay and for matrix components production (proteins and carbohydrates) using the BCA and phenol-sulfuric tests, respectively. The effect of different antifungals on biofilm formation was studied. Results: in the children's group, a predominance of C. krusei (81%) was observed, while, among adults, the main species was C. albicans (59%). Most strains showed a reduced response to antimicrobial drugs when in biofilm form (p < 0.01). Moreover, it was observed that strains isolated from children produced more matrix, with higher levels of protein and polysaccharides. Conclusions: children were more likely to be infected by NCACs than adults. More importantly, these NCACs were able to form biofilms richer in matrix components. This finding is of clinical importance, particularly in pediatric care, since stronger biofilms are highly associated with antimicrobial resistance, recurrent infections, and higher therapeutic failure.